ANALYSIS OF PUBLIC LEISURE POLICIES IN VULNERABLE SPACES IN THE CITY OF SENADOR CANEDO - GO (CIPEEX, 2022)
LEISURE IS A FUNDAMENTAL RIGHT, PROVIDED FOR IN ARTICLE 6 OF THE FEDERAL CONSTITUTION, WHICH "TRANSLATES INTO A PRIVILEGED DIMENSION OF HUMAN EXPRESSION WITHIN A CONQUERED TIME MATERIALIZED THROUGH A CREATIVE PERSONAL EXPERIENCE, OF PLEASURE THAT IS NOT REPEATED IN SPACE TIME WHOSE MAIN AXIS IS PLAYFULNESS" (BRUMANTE, 1998). THE FEDERAL CONSTITUTION ESTABLISHES AN ORDER FOR THE STATE TO ENFORCE THE RIGHT TO LEISURE FOR ALL CITIZENS IN THE NATIONAL, STATE, AND MUNICIPAL SPHERES (BRASIL, 1998). HOWEVER, THIS RIGHT OFTEN PRIORITIZES THE NOBLE AREAS OF THIS MUNICIPALITY AND EXCLUDES THE VULNERABLE AREAS OF THE CITY. IN THIS SENSE, THE PRESENT WORK AIMS AT EVALUATING AND ANALYZING WHETHER THIS RIGHT HAS BEEN EQUALLY PROVIDED TO THE POPULATION BY THE PUBLIC POWER OF SENADOR CANEDO. TO REACH THE DESIRED RESULTS IT WAS ESTABLISHED THE FOLLOWING SPECIFIC OBJECTIVES: A) DISCUSS THE CONSTITUTIONAL PROVISION ABOUT THE RIGHT TO LEISURE; B) DISPOSE ABOUT AND CONCEPTUALIZE LEGALLY AND DOCTRINALLY LEISURE; C) ANALYZE WHETHER THE MUNICIPAL GOVERNMENT OF SENADOR CANEDO, GO, PROVIDES EQUAL ACCESS TO LEISURE TO ALL AREAS OF THE CITY. TO THIS END, THE FOLLOWING QUESTION WAS ESTABLISHED AS THE CENTRAL PROBLEM: DO ALL AREAS OF THE CITY OF SENADOR CANEDO PROVIDE EQUAL ACCESS TO LEISURE? THE METHODOLOGICAL CONSTRUCT USED TO OBTAIN DATA FOR THIS RESEARCH CONSISTED OF FIELD, EXPLORATORY AND EXPLANATORY RESEARCH, BESIDES BIBLIOGRAPHICAL RESEARCH. THE PRESENT STUDY FINDS A HIGH DEGREE OF IMPORTANCE IN THE LEGAL, SCIENTIFIC AND SOCIAL FIELDS, AS IT AIMS AT APPROACHING THE RIGHT OF ACCESSIBILITY TO LEISURE IN AREAS OF SOCIAL VULNERABILITY IN THE CITY OF SENADOR CANEDO, A SUBJECT THAT HAS NEVER BEEN EXPLORED, BRINGING SCIENTIFIC AND INFORMATIVE CONTRIBUTIONS TO THE POPULATION, AND MAY EVEN BE THE OBJECT OF A LEGISLATIVE PROPOSAL. THUS, IT IS IMPORTANT TO DISCUSS THE PROPOSED THEME, SINCE THE RESULTS OBTAINED POINT TO A CLEAR DISCREPANCY BETWEEN THE PUBLIC LEISURE OFFERED IN MORE FAVORED AREAS AND THE OUTSKIRTS, WHICH HARMS NOT ONLY THE CONSTITUTIONAL RIGHT TO LEISURE, BUT ALSO THE CONSTITUTIONAL RIGHT TO EQUALITY "EVERYONE IS EQUAL BEFORE THE LAW, WITHOUT DISTINCTION" (BRASIL 1988). THUS, THE RESULTS OBTAINED WERE: A) IN THE NEIGHBORHOODS STUDIED (BURITI, PARASO 1 AND 2) THERE IS A TOTAL LACK OF PUBLIC POLICIES RELATED TO LEISURE; B) IN NOBLE AREAS OF THE CITY THERE ARE PUBLIC POLICIES RELATED TO LEISURE, WHICH SHOWS A VIOLATION OF THE CONSTITUTIONAL RIGHT TO EQUALITY AND LEISURE; C) THUS, IT IS NECESSARY AN ACTIVE POSTURE OF THE MUNICIPAL GOVERNMENT TO SOLVE THIS PROBLEM. IT IS UNDERSTOOD THAT, FROM THE DATA THAT WILL BE REVEALED THROUGH THIS STUDY, IT IS UP TO THE GOVERNMENT AND THE COMMUNITY TO RETHINK THE APPLICABILITY OF THE MUNICIPAL BUDGET, CONSIDERING THAT THE PROMOTION OF LEISURE CONTRIBUTES SIGNIFICANTLY TO THE REDUCTION OF VIOLENCE.&NBSP;
Keywords: Right to City; Right to Leisure; Public Policies